Post-operative Pain after Different Root Canal Irrigant Activation Methods in Patients with Acute Apical Periodontitis (Randomized Clinical Trial) - Elzainy, Passant; Hussein, Wael; Hashem, Ahmed; Badr, Mahmoud (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective To evaluate the degree of postoperative pain in patients with necrotic teeth with symptomatic apical periodontitis after applying ultrasonic irrigation or manual dynamic agitation. Methods Seventy-eight patients diagnosed with necrotic mandibular first molar with symptomatic apical periodontitis were randomly allocated into 1 of 3 separate groups (n=26); Manual Dynamic Agitation group, Ultra X group, or NaviTip group (control). After a single-visit root canal treatment and a specific method of agitation, depending on each group, the patients were given a questionnaire on which they would mark the degree of pain in a scale from 0 to 10 at 6, 12, 24, 48, 72 hours and 7 days post-operative. Data were statistically analyzed with a significance level of P ≤ 0.05. Results Final irrigation protocol including Ultrasonic agitation and NaviTip (control) groups showed significantly lower values of pain than the MDA group. There was a reduction in pain values by time in all groups. Conclusion There was significantly less pain associated with passive ultrasonic agitation and side vented needle (NaviTip) irrigation compared to Manual Dynamic Agitation.